2020
DOI: 10.3390/molecules25153389
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Chemical Attack of Hybrid Fly Ash-Based Alkali-Activated Concretes

Abstract: The environmental impacts related to Portland cement production in terms of energy consumption, the massive use of natural resources and CO2 emissions have led to the search for alternative cementitious materials. Among these materials, alkali-activated cements based on fly ash (FA) have been considered for concrete production with greater sustainability. In the present article, the chemical durability properties (resistance to sulphates, chloride permeability, and resistance to carbonation) of a hybrid alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Industrially produced hybrid H-Cement, is characterized by ready grindability, to a specific surface of 6,100 cm 2 /g, an output of 22 t/h and an energy consumption of 63 kWh/t, compared to an output of 12 t/h and energy consumption of 115 kWh/t for conventional CEM I 52.5 R cement with a specific surface of 5,100 cm2/g produced in the same facility (Martauz et al, 2016). In recent years, much information has been published on the hydration mechanisms in hybrid cements (such a H-cement) and their physical and mechanical properties, along with their durability (Garcia-Lodeiro et al, 2018;Fernández-Jiménez et al, 2019b;Askarian, et al, 2018;Valencia-Saavedra and de Gutiérrez, 2020;Xue et al, 2021).…”
Section: One-part Alkali Activated Binders With Ground Not Synthetic Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Industrially produced hybrid H-Cement, is characterized by ready grindability, to a specific surface of 6,100 cm 2 /g, an output of 22 t/h and an energy consumption of 63 kWh/t, compared to an output of 12 t/h and energy consumption of 115 kWh/t for conventional CEM I 52.5 R cement with a specific surface of 5,100 cm2/g produced in the same facility (Martauz et al, 2016). In recent years, much information has been published on the hydration mechanisms in hybrid cements (such a H-cement) and their physical and mechanical properties, along with their durability (Garcia-Lodeiro et al, 2018;Fernández-Jiménez et al, 2019b;Askarian, et al, 2018;Valencia-Saavedra and de Gutiérrez, 2020;Xue et al, 2021).…”
Section: One-part Alkali Activated Binders With Ground Not Synthetic Productsmentioning
confidence: 99%
“…In recent years, much information has been published on the hydration mechanisms in hybrid cements (such a H-cement) and their physical and mechanical properties, along with their durability ( Garcia-Lodeiro et al, 2018 ; Fernández-Jiménez et al, 2019b ; Askarian, et al, 2018 ; Valencia-Saavedra and de Gutiérrez, 2020 ; Xue et al, 2021 ).…”
Section: Raw Materials Processing Industrial-scale Alkali Activated Binders Manufacturementioning
confidence: 99%
“…The durability against the sulfate attack is also dependent on the cation in the solution. Alencia-Saavedra et al reported that the alkaliactivated FA/OPC sample was more durable in Na 2 SO 4 solution than MgSO 4 solution [99].…”
Section: Chemical Resistancementioning
confidence: 99%
“…Since the attack of H 2 SO 4 is coupled with sulfate, it is one of the most harmful acids for cement-based materials [ 17 ]. Sulfate attack is a prominent component in the deterioration of cement-based materials and affects their durability because of the chemical assault by sulfates and the physical attack owing to salt crystallization [ 18 , 19 ]. The breakdown of CSH leads to the formation of additional compounds, which contribute to the durability issues of cement-based materials [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate attack is a prominent component in the deterioration of cement-based materials and affects their durability because of the chemical assault by sulfates and the physical attack owing to salt crystallization [ 18 , 19 ]. The breakdown of CSH leads to the formation of additional compounds, which contribute to the durability issues of cement-based materials [ 18 ]. Hence, it is important to study how acid attacks could shorten the lifespan of cement-based materials.…”
Section: Introductionmentioning
confidence: 99%